THE INFLUENCE OF THE BIOMAS OF MELATI AIR (Echinodorus paleafolius) AND TERATAI (Nyphaea firecrest) ON PHOSPHATE CONTENT, BOD, COD, TSS, AND DEGREE OF MASTER LIQUID WASTE OF LAUNDRY - Regina Tutik Padmaningrum; Tien Aminatun; Yuliati Yuliati (Jurnal Penelitian Saintek, 2014)
Laundry liquid waste containing residual detergent, deodorant, fabric softener, bleach, and methylene blue active compounds degraded difficult and dangerous for the health of the environment. Almost all wastewater is discharged home laundry business through sewers or septitank untreated or diluted beforehand so that would pollute the environment. One way toreduce the chemicals present in the wastewater is to phytoremediation. The study aims to determine the effect of water jasmine and lotus biomass on the content of phosphate, the value of BOD, COD, TSS, and pH of laundry wastewater is treated. The independent variables were the type of biomass (water jasmine, lotus) and time of application of the waste. Dependent variables include phosphate levels, DO, BOD, COD, TSS, and pH. Stages of research include 1) cleaning the roots and stems of water jasmine and lotus plants, 2) the process of acclimatization, 3) the application of the plant for a month, and 4) measurement of the dependent variable. The results showed phytoremediation using water jasmine plants can reduce levels of 172.1748 ppm phosphate, lowering the value of COD is 446.890 mg/L, lower the BOD value of 38.748 mg/L, and the lower the pH by 0.18 units of laundry wastewater, value COD, BOD and lowers the pH of 0.18 units of laundry wastewater. Lotus plant can not be used as a laundry liquid waste processing plants in phytoremediation.